IN COMPETITION, MUNICIPAL MEDICAL ESTABLISHMENTS LOSE TO THE PRIVATE ONES - S. G. Demchenko; A. L. Faizkhanova (Russian Journal of Economics and Law, 2013)
Objective: revealing the factors of attractiveness of medical services rendered by municipal and private medical establishments. Methods: field marketing research basing on random personal interviews on formalized questionnaires and comparative analysis of satisfaction of medical services consumers. Results: it is found that 68% of respondents are for various reasons not satisfied by medical services rendered by municipal establishments. The main reasons for dissatisfaction are waiting for the doctor’s appointment for more than an hour, lack of specialists, service quality, indifferent attitude of a doctor to the patient, and others. Scientific novelty: the most attractive features of commercial medical centres are determined, among them the absence of queues, availability of specialists, quality of services. Practical value: achievements of commercial medical establishments, attracting clients by higher quality services, serve as the basis for using experience by municipal medical establishments.